Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1601-183x.2010.00664.x
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric self-infusion of ethanol in high- and low-drinking mouse genotypes after passive ethanol exposure

Abstract: Two experiments examined the effect of 5 days of passive exposure to ethanol (or water) on later self-infusion of ethanol or water via surgically implanted intragastric (IG) catheters in mouse genotypes previously shown to drink high (C57BL/6J, HAP2) or low (DBA/2J, LAP2) amounts of ethanol in home-cage continuous-access two-bottle choice procedures. Intragastric ethanol selfinfusion was affected by both genotype and a history of passive ethanol exposure, with greater intakes in the high-drinking genotypes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 37 publications
6
58
1
Order By: Relevance
“…Of particular interest, the study involved using this model to examine ethanol self-administration in mouse inbred strains that exhibit high (C57BL/6J) versus low (DBA/2J) ethanol preference, as well as mouse lines selectively bred for high (HAP2) versus low (LAP2) ethanol preference. Increased ethanol self-administration in the model was demonstrated in all mice, whether they typically exhibit high (C57BL/6J, HAP2) or low (DBA/2J, LAP2) ethanol intake under baseline conditions (Fidler et al, 2011). Thus, intragastric self-administration of ethanol was similar for all genotypes after a period of forced ethanol infusions even though these genotypes greatly differ in their acceptance of ethanol when it is presented for oral consumption.…”
Section: Operant Ethanol Self-administration In Dependent Micementioning
confidence: 99%
See 4 more Smart Citations
“…Of particular interest, the study involved using this model to examine ethanol self-administration in mouse inbred strains that exhibit high (C57BL/6J) versus low (DBA/2J) ethanol preference, as well as mouse lines selectively bred for high (HAP2) versus low (LAP2) ethanol preference. Increased ethanol self-administration in the model was demonstrated in all mice, whether they typically exhibit high (C57BL/6J, HAP2) or low (DBA/2J, LAP2) ethanol intake under baseline conditions (Fidler et al, 2011). Thus, intragastric self-administration of ethanol was similar for all genotypes after a period of forced ethanol infusions even though these genotypes greatly differ in their acceptance of ethanol when it is presented for oral consumption.…”
Section: Operant Ethanol Self-administration In Dependent Micementioning
confidence: 99%
“…As in the case for rats, studies have shown mice to respond for ethanol as a positive reinforcer when it is delivered orally (Meisch, 2001), intravenously (Grahame & Cunningham, 1997), and directly into the stomach via intragastric infusion (Fidler et al, 2011). While early studies showed that ethanol responding and intake is enhanced in food-deprived mice (Middaugh & Kelley, 1999), ethanol was demonstrated to be an effective positive reinforcer in non-food deprived mice as well (Ford, Fretwell, Mark, & Finn, 2007; Middaugh, Lee, & Bandy, 2000).…”
Section: Operant Ethanol Self-administration In Micementioning
confidence: 99%
See 3 more Smart Citations